2010
DOI: 10.1016/j.cell.2010.02.037
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Cellular Approaches for Diversifying and Extending Optogenetics

Abstract: SUMMARY Optogenetic technologies employ light to control biological processes within targeted cells in vivo with high temporal precision. Here, we show that application of molecular trafficking principles can expand the optogenetic repertoire along several long-sought dimensions. Subcellular and transcellular trafficking strategies now permit (1) optical regulation at the far-red/infrared border and extension of optogenetic control across the entire visible spectrum, (2) increased potency of optical inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
945
2
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 915 publications
(980 citation statements)
references
References 79 publications
13
945
2
7
Order By: Relevance
“…Last month, Deisseroth reported a system in mice that could make detailed knowledge of promoters unnecessary: two viruses containing separate genetic constructs are injected into two connected brain regions. Only neurons that run between the two regions will receive doses of both constructs, which then interact to express the opsin 5 . Boyden is designing a light source that would weigh a fraction of a gram so that animals can walk around freely rather than being tethered to a fibre-optic cable.…”
Section: Experts On Handmentioning
confidence: 99%
“…Last month, Deisseroth reported a system in mice that could make detailed knowledge of promoters unnecessary: two viruses containing separate genetic constructs are injected into two connected brain regions. Only neurons that run between the two regions will receive doses of both constructs, which then interact to express the opsin 5 . Boyden is designing a light source that would weigh a fraction of a gram so that animals can walk around freely rather than being tethered to a fibre-optic cable.…”
Section: Experts On Handmentioning
confidence: 99%
“…This would constitute another method of gene control in vivo and advance the field of optogenetics. 24,25 The gene with the next highest levels of activation as studied by qRT-PCR was that encoding the cytokine IL6 which showed a 119-fold increase at the laser spot and a 20-fold increase in the adjacent laser region. While Cxcl3 was the only chemokine analyzed with qRT-PCR, the microarrays indicated that there was a large number of members of this group that were up-regulated by 4-fold or more due to laser thermal stress.…”
Section: Discussionmentioning
confidence: 99%
“…• Miniaturise interfaces for use on small nerves adjacent to organs to enable work in rodent disease models o Develop cuffs that optimally interface with nerves at <100µm diameter, recognising the signal-to-noise and charge injection issues associated with recording and stimulation using micron-scale electrode geometries [20][21][22][23][24][25][26] o Develop high-density arrays with micro-scale features and integrated active electronics which allow stable electrical interfacing with 10-100 channels in small nerves, while minimising axonal damage from displacement 27 …”
Section: Research Imperativesmentioning
confidence: 99%